ESP Needs Analysis at the Moroccan University: Renewable Energy Engineering Students at EST Fes as a Case Study - Hanae AIT HATTANI (Journal of English Language Teaching and Linguistics, 2019)
With English becoming the world’s lingua franca and the proliferating scientific and technological advances, English language education has been gradually shifting from its classical applications such as EFL (English as a foreign language) or ESL (English as a second language) toward new paradigms like English for specific purposes (ESP). The most important and problematic question in ESP teaching and learning is whether the course is effective or not. ESP is student-task oriented, thus, measuring its effectiveness is strongly related to measuring learners’ attitudes, needs, expectations, satisfaction, and achievement. For this purpose, this study attempted to investigate ESP needs analysis of Moroccan university students, case study of renewable energy engineering students at the Higher School of Technology (ESTF).  The research was conducted using quantitative surveys d. The data was gathered from 30 undergraduate renewable energy engineering students. The study findings confirmed that the participant students have highly favorable attitudes towards English language for both their personal and professional careers. However, the survey results indicated that these students have some difficulties with English language productive skills, namely speaking and writing, in addition to some other sub-skills. Therefore, this research suggests a reform at the level of ESP teaching and learning curricular, focusing on the incorporation of innovative approached and methods that aims at enhancing students’ language acquisition and competency.